Intramedullary solitary fibrous tumor: a benign form of hemangiopericytoma? : case report and review of the literature - Bruder, Markus; Capper, David (World neurosurgery, 2015)
Background Solitary fibrous tumors (SFTs) are benign tumors of the soft tissue occurring anywhere in the human body but arise predominantly in the visceral pleura. SFTs of the central nervous system are rare, especially when they occur within the spinal cord. Case Description We present a case of an 83-year-old female patient presenting with acute spastic paralysis of the lower extremities after a history of progressive weakness and incontinence. Magnetic resonance imaging (MRI) findings were typical for meningioma, but an intradural, mainly intramedullary tumor was found at the first operation. A second operation was performed under neurophysiological monitoring, and complete removal of the tumor was achieved. Neurological conditions improved after the procedure, but the patient remained paraparetic. Histological and immunohistochemical findings revealed an SFT. Conclusions There is evidence that SFTs and hemangiopericytomas (HPCs) are not different entities but should be considered as different graduations of a common spectrum. The extent of resection is a prognostic factor for recurrence-free survival in SFT; therefore we recommend surgery with complete resection whenever possible depending on the results of mandatory intraoperative neurophysiological monitoring in these cases.
Gesehen am 11.04.2017